2011
DOI: 10.1590/s1679-39512011000300011
|View full text |Cite
|
Sign up to set email alerts
|

A inclusão de catadores em programas de coleta seletiva: da agenda local à nacional

Abstract: ResumoO presente trabalho tem como objetivo discutir como a inclusão social e produtiva de catadores de materiais recicláveis, antes presente apenas na agenda de políticas públicas locais, alcançou a agenda governamental nacional. Recorre-se à discussão teórica de múltiplos fluxos, de Kingdon (1995), apontando suas limitações para a análise do fenômeno investigado. Os procedimentos metodológicos adotados foram: revisão bibliográfica, observação participante em eventos, levantamento de dados secundários, conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
16

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 7 publications
0
6
0
16
Order By: Relevance
“…While this activity has promoted a significant increase in global macroeconomic indicators that generally benefit the world's population, the expansion has also had deleterious side effects, one of which is that it has contributed to unprecedented environmental degradation that exceeds bearable limits (SEIFFERT, 2009;GOUVEIA, 2012). According to Pereira and Teixeira (2011), the progress that was experienced after the industrial revolution is unsustainable and has had perceptible negative consequences, such as pollution of the aquatic ecosystem, degradation of air quality due the burning of fossil fuels, and accumulation of excessive waste. Recognizing these negative effects, the main environmental institutes and their researchers began to intensely debate these problems.…”
Section: Introductionmentioning
confidence: 99%
“…While this activity has promoted a significant increase in global macroeconomic indicators that generally benefit the world's population, the expansion has also had deleterious side effects, one of which is that it has contributed to unprecedented environmental degradation that exceeds bearable limits (SEIFFERT, 2009;GOUVEIA, 2012). According to Pereira and Teixeira (2011), the progress that was experienced after the industrial revolution is unsustainable and has had perceptible negative consequences, such as pollution of the aquatic ecosystem, degradation of air quality due the burning of fossil fuels, and accumulation of excessive waste. Recognizing these negative effects, the main environmental institutes and their researchers began to intensely debate these problems.…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, Kingdon's matrix (1995) has also served as a theoretical lens for further studies on agenda-setting in public policies in Brazil. Capella (2008), Pereira and Teixeira (2011) and Nagem and Silva (2013) showed that there is common ground in many national public policies that emerged from the confluence of social, political and economic forces even when actors, content, periods and contexts are totally different. To give support to the analysis below, this section is devoted to a conceptual approach of the MSM.…”
Section: Agenda-setting In Public Policy -A Brief Review Of Literaturementioning
confidence: 99%
“…Eles seriam agentes dispostos a investir tempo e energia em acoplar os diferentes fluxos (Pereira & Teixeira 2011). Entre as habilidades destes empreendedores estariam: legitimidade sobre um assunto (derivada de suas especialidades, capacidade de falar em nome dos outros ou posição de poder), conexões políticas, capacidade de negociação e persistência (Kingdon 1984).…”
Section: Ii3 Uma Breve Descriçãounclassified